Atomic layer deposition of high-k dielectric films for diamond mos structures - Jaggernauth, Aneeta (2022)
Changes in the expected performance of electronic devices in extreme applications have heavily influenced investigation into Si-substitute materials having the ability to meet these demands. Two examples are especially pertinent to the performance of metal oxide semiconductor (MOS) devices. The first is the move towards films with high dielectric constants (high-κ); as more devices are integrated into the same circuit to facilitate the numerous system operations, the size of each device is greatly reduced necessitating exploration into more suitable options for replacing SiO₂ and Al₂O₃ films in transistors and capacitors to effectively control semiconductor charge carriers and prevent charge leakage. The second is investigation into ultra-wide band gap (UWBG) semiconductor materials to efficiently permit device operation in extreme conditions. Polycrystalline diamond (PCD) is an UWBG material that provides a costeffective option for MOS devices, but it has yet to be fully studied for these applications. The combination of high-κ films on PCD for MOS components has been limited to Al₂O₃ despite the ability to fabricate films with higher κ values by atomic layer deposition (ALD), a technique which imparts advantages of self-limiting and saturation reactions with atomic layer control, thus being advantageous for studying interfacial properties. The work in this thesis therefore explores dielectric oxides of Al (AlO), Ta (TaO) and Ti (TiO) for use in MOS structures, with PCD films utilized as the semiconducting layer. Novelty is achieved by investigating interfacial properties and fabrication issues, more specifically, the mechanical stability of AlO films on chemically different PCD surfaces, challenges related to the ALD of TaO films, energy band alignment between TiO and PCD, and the behaviour of MOSFETs utilizing TiO dielectrics on B-doped diamond (BDD). In all, this thesis provides a body of research pertinent to the use of ALD high-κ oxides for use in diamondbased MOS devices.